A randomized, controlled trial on fenofibrate in primary biliary cholangitis patients with incomplete response to ursodeoxycholic acid. (July 2022) - Li, Chunlei; Zheng, Kunyu; Chen, Yiran; He, Chengmei; Liu, Suying; Yang, Yunjiao; Li, Mengtao; Zeng, Xiaofeng; Wang, Li; Zhang, Fengchun
Introduction: About one-third of primary biliary cholangitis (PBC) patients do not exhibit complete response to ursodeoxycholic acid (UDCA). Some of these patients were reported to benefit from the combination therapy of fibrates and UDCA, but more clinical evidence is required. In this study, we conducted a randomized, controlled trial on the safety and efficacy of fenofibrate in the treatment of patients with PBC. Methods: Forty-eight PBC patients with incomplete response to UDCA were enrolled and randomly assigned to two groups (24 in the experiment group and 24 in the control group). For the experimental group, the patients were administered 13–15 mg/kg/day UDCA in combination with 200 mg/day fenofibrate. For the control group, the patients continued to receive UDCA at 13–15 mg/kg/day. The patients were followed up for at least 12 months. The serum levels of alkaline phosphatase (ALP), gamma-glutamyl transferase (γ-GT), aspartate aminotransferase (AST), and other biochemical parameters were measured at 3, 6, and 12 months during the trial to assess patient conditions. Results: At 12 months, 20.8% of the patients in the experimental group had all three indexes of serum ALP, γ-GT, and total bilirubin normalized, while 0% of patients in the control group reached the primary outcome (difference, 20.8 percentage points; 95% CI, 4.6–37.0). 54.2% of the patients had normal ALP levels in the experimental group and 4.2% in the control group (difference, 50 percentage points; 95% CI, 28.5–71.5). The experimental group had greater improvement of ALP ( p  < 0.001) and IgG ( p  = 0.026) than the control group. The biochemical indexes of the patients in the experimental group also significantly improved during the treatment of fenofibrate. Conclusion: Addition of fenofibrate can improve biochemical indexes of PBC patients who had an incomplete response to UDCA. Reversible elevation of serum creatine and transaminases is observed in some patients. The trial was registered in the Chinese Clinical Trial Registry (ChiCTR) as ChiCTR1800020160 (protocol available online:http://www.chictr.org.cn/showproj.aspx?proj=32443 ).